Democratic enlargement : the Clinton doctrine. - BRINKLEY, Douglas (1997)
Explains the concept of 'democratic enlargement' which President Clinton used to elucidate his foreign policy agenda. The phrase embraces the US's three foreign policy priorities, viz. updating and restructuring American military and security capabilities, elevating the role of economics in international affairs, and promoting democracy abroad.